Exploring the Dynamics of Online Influence: An analysis of how online influencers optimise their influence on their audience when bringing awareness to socio-environmental issues. - Strauss, James (The IIE, 2018)
The online influencer marketing sphere within South Africa is a fairly new and unexplored phenomenon that has only started gaining traction over the last few years. Because of the pressure on South African online influencers to catch up to their international peers, it has become necessary to explore the dynamics of the online influencer marketing sphere in South Africa. This research study leans on The Social Learning Theory by Albert Bandura (1971) which assisted in the analysis of the ways in which online influencers optimise their influence on their audience when bringing awareness to socio-environmental issues. In alignment with a qualitative research design, this study administered in-depth interviews to a sample of 3 active and prominent online influencers in South Africa. The findings of the research pointed out that an adherence to pop-culture content creation trends and the maintenance of brand loyalty through constant interaction with audience members are vital factors for a positive return on engagement. By establishing a positive brand tone of voice and refraining from negative communication techniques, online influencers will strengthen their position in the minds of their audience members and thus increase their likelihood of optimal engagement, when creating awareness around socio-environmental issues.
Keywords: Online influencer marketing; Marketing; Pop culture; Online engagement; Personal branding; Branding